Measurement of Atmospheric Extinction Coefficient at Thai National Observatory (TNO) - Sookjai, Donrudee; Sonkeaw, Thiranan; Panomprai, Jansawang; Pongpraisirikul, Sauwaporn; Surophan , Phanphaka; Thaimai, Prorawit; Rattanasoon, Somsawat; Macatangay, Ronald (Burapha Science Journal, 2026)
The apparent intensity and color of starlight can be dwindled by the scattering and absorption of the earth's atmosphere. This is called atmospheric extinction, which depends on atmospheric conditions of the observing site and altitude of the targets. This research aims to study the extinction of starlight at the Thai National Observatory (TNO), with an elevation of 2,457 meters, latitude 18.57 ̊N and longitude 98.48 ̊E during a clear sky condition in November 2018. The atmospheric extinction coefficient was investigated using a reflecting telescope with a diameter of 2.4 meters, whose images were captured by a CCD camera through light filters and photometric analysis was carried out using the IRIS software package. The results showed that the atmospheric extinction coefficients were 0.57 ± 0.023 0.33 ± 0.025 0.20 ± 0.013 0.12 ± 0.013 and 0.11 ± 0.065 (magnitudes/airmass) through the wavelength filters of U, B, V, R and I, respectively. There are comparable to the atmospheric extinctions previously reported from observatories in other countries. The atmospheric extinction coefficients were also decomposed into ozone absorption, Rayleigh scattering and Mie scattering components. Ozone absorption affects primarily to the visible wavelength Rayleigh scattering dominates the ultraviolet bands but the extinction decreases rapidly as the wavelength increases. The relation of extinction due to Mie scattering from atmospheric aerosols as a function of wavelength was determined empirically and is given by . This method can be useful in determining aerosol optical properties on a routine basis especially during the nighttime when standard measurement techniques are not viable. The atmospheric extinction coefficient can be used as preliminary compensation data for the TNO.